The influence of caffeine supplementation on resistance exercise: A review - Grgic, J.; Mikulic, P.; Schoenfeld, B. J.; Bishop, D. J.; Pedisic, Z. (Sports Medicine, 2019)
This paper aims to critically evaluate and thoroughly discuss the evidence on the topic of caffeine supplementation when performing resistance exercise, as well as provide practical guidelines for the ingestion of caffeine prior to resistance exercise. Based on the current evidence, it seems that caffeine increases both maximal strength and muscular endurance. Furthermore, power appears to be enhanced with caffeine supplementation, although this effect might, to a certain extent, be caffeine dose- and external load-dependent. A reduction in rating of perceived exertion (RPE) might contribute to the performance-enhancing effects of caffeine supplementation as some studies have observed decreases in RPE coupled with increases in performance following caffeine ingestion. However, the same does not seem to be the case for pain perception as there is evidence showing acute increases in resistance exercise performance without any significant effects of caffeine ingestion on pain perception. Some studies have reported that caffeine ingestion did not affect exercise-induced muscle damage, but that it might reduce perceived resistance exercise-induced delayed-onset muscle soreness; however, this needs to be explored further. There is some evidence that caffeine ingestion, compared with a placebo, may lead to greater increases in the production of testosterone and cortisol following resistance exercise. However, given that the acute changes in hormone levels seem to be weakly correlated with hallmark adaptations to resistance exercise, such as hypertrophy and increased muscular strength, these findings are likely of questionable practical significance. Although not without contrasting findings, the available evidence suggests that caffeine ingestion can lead to acute increases in blood pressure (primarily systolic), and thus caution is needed regarding caffeine supplementation among individuals with high blood pressure. In the vast majority of studies, caffeine was administered in capsule or powder forms, and therefore the effects of alternative forms of caffeine, such as chewing gums or mouth rinses, on resistance exercise performance remain unclear. The emerging evidence suggests that coffee might be at least equally ergogenic as caffeine alone when the caffeine dose is matched. Doses in the range of 3-9 mg·kg-1 seem to be adequate for eliciting an ergogenic effect when administered 60 min pre-exercise. In general, caffeine seems to be safe when taken in the recommended doses. However, at doses as high as 9 mg·kg-1 or higher, side effects such as insomnia might be more pronounced. It remains unclear whether habituation reduces the ergogenic benefits of caffeine on resistance exercise as no evidence exists for this type of exercise. Caution is needed when extrapolating these conclusions to females as the vast majority of studies involved only male participants.